Strand 2: A Tele-seminar on Drawing with AutoCAD: Design, Production and Pilot Implementations - Rigopoulos, Dionysis R. (Proceedings of the International Conference on Networked Learning, 1998)
This paper describes the design, the production of supporting software and the pilot implementation of a continuing education tele-seminar on drawing with AutoCAD, at the National Technical University of Athens (NTUA). The seminar was completed at the end of December 1997: it was part of a two year innovative project on tele-education in CAD/COM/CIM (Computer-Aided Design/Computer aided manufacturing/ Computer integrated Manufacturing), co-funded bu the European Social Fund and the NTUA. Over two hundred and sixty 'students' registered for the seminar, the majority of whom were professional engineers and architects. Maore than half of the participants were from Athens. The distribution of the others covered all geographic departments of Greece. The author was responsible for the design material production and teaching of this seminar.